Mesenchymal stem cell therapy for treatment of osteoradionecrosis of mandible in head and neck surgery patients - A way forward into the future with promising clinical Outcomes - Ainulakbar Mughal; Merhaba Aftab; Abdul Basit Shah Vardag; Zubair Khan; Hamdan Ahmed Pasha; Muhammad Sohail Awan (Journal of the Pakistan Medical Association, 2023)
Managing osteoradionecrosis is an integral part of complication management in head and neck cancer patients. While essentially an infection, the management of this complication has a considerable task for head and neck surgeons. While various measures have been discussed for the management, stem cells injection therapy is a potential management option. Mesenchymal stem cell therapy provides the local tissue with growth factors and proliferative cells that can aid a radiated tissue in the healing process. The article intends to review the bedrock of the pathology, ranging from pathophysiological and the epidemiological concerns to sparking a potential discussion on the use of mesenchymal stem cell therapy in osteoradionecrosis of mandible in head and neck cancer surgery and thus the ensuing future of the regenerative medicine. Continued...